Effect of heat stress on some plasma electrolytes of layer hens reared during summer in hot-humid climate and administered with vitamins C and E. - Ajakaiye, J. J.; Perez-Bello, A.; Cuesta-Mazorra, M.; Garc?a D?az, J. R.; Mollineda-Trujillo, A. (Cuban Journal of Agricultural Science, 2010)
This study was carried out to investigate the effects of vitamins C and E on some plasma electrolytes of layer hens reared during summer in hot-humid climate. Seven hundred and twenty White Leghorn (L33) birds and 39 weeks old were divided into four groups of 180. One group was fed basal diet (control) and treatment groups were fed basal diet supplemented with 150 mg of l-ascorbic acid/kg of diet (Vit. C group), 150 mg of ?-dl-tocopherol acetate/kg of diet (Vit. E group), while the last group was supplemented 150 mg of l-ascorbic acid/kg of diet plus 150 mg of ?-dl-tocopherol acetate/kg of diet (Vit C + E group). Plasma calcium and phosphorus concentrations were lower (P < 0.05) in the control group, compared to the supplemented groups. Conversely, magnesium concentration was significantly (P < 0.05) higher in all experimental groups when compared to vitamin C treated group. Furthermore, potassium and sodium concentrations were significantly (P < 0.05) higher in all the treated groups, compared to the control. In microelements, iron concentration was significantly (P < 0.05) lower in the control group compared to all the supplemented groups, with the higher difference recorded in vitamins C and E groups. However, copper and zinc were not affected by the treatments. The results suggest that supplementation of the antioxidant vitamins alleviated the negative effect of heat stress on the exposed birds, as it enhanced the supply and/or stability of plasma electrolytes. It is, therefore, recommended that both antioxidants be incorporated into the feed regime of layer hens, particularly during the hot summer period. Keywords: Layer hens, macro and microelements, vitamin C, vitamin E, heat stress.